Method for manufacturing menthol by hydrogenation of thymol to menthone and hydrogenation on menthone to menthol. - Dreisbach, Claus; Jentsch, Jörg-Dietrich; Heuer, Lutz; Wasserscheid, Peter; Rittsteiger, Anne; Mechelhoff, Martin (2014)
The invention presents a process for prodn. of 2-isopropyl-5-Me cyclohexanol (D, L-menthol) by hydrogenation of thymol to menthone and following hydrogenation to D, L-menthol. [on SciFinder(R)]
Keywords: menthol prodn process catalyst thymol hydrogenation menthone intermediate